Case of gel immersion endoscopy: Efficacy of identification and achieving hemostasis for diverticular hemorrhage in the sigmoid colon. Issue 4 (21st February 2022) - Teshima, Hajime; Yamashita, Ken; Oka, Shiro
Abstract : Watch a video of this article.